Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.30110.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Seasonal embolism and xylem vulnerability in deciduous and evergreen Mediterranean trees influenced by proximity to a carbon dioxide spring - Tognetti, Roberto; Longobucco, Anna; Raschi, Antonio (Tree Physiology, 1999)
We investigated how proximity to natural CO2 springs affected the seasonal patterns of xylem embolism in Quercus ilex L., Quercus pubescens Willd., Fraxinus ornus L., Populus tremula L. and Arbutus unedo L., which differ in leaf phenology and wood anatomy. Xylem embolism was evaluated in both artificially dehydrated branches and in hydrated apical branches collected at monthly intervals during a 20-month sampling period. Initial specific hydraulic conductivity was also evaluated. We found species-dependent differences in xylem hydraulic properties in response to elevated CO2 concentration. Populus tremula was the most embolized and A. unedo was the least embolized of the species examined. Effects of elevated CO2 were significant in Q. pubescens, P. tremula and A. unedo, whereas the overall response to elevated CO2 was less evident in F. ornus and Q. ilex. Specific hydraulic conductivity differed among species but not between sites, although the interaction between species and site was significant. Differences in xylem vulnerability between trees growing near to the CO2 spring and those growing in control areas were small. Although differences in hydraulic properties in response to elevated CO2 concentration were small, they may be of great importance in determining future community composition in Mediterranean-type forest ecosystems. The possible causes and ecological significance of such differences are discussed in relation to elevated CO2 concentration and other environmental conditions.
10.1093/treephys/19.4-5.271
Keywords: cavitation; CO2 springs; diffuse-porous; Global change; hydraulic conductivity; Mediterranean-type ecosystems; ring-porous; semiring-porous

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S; Miglietta, Franco; Raschi, Antonio; Körner, C (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S.; Miglietta, Franco; Raschi, Antonio; Körner, C. (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex